Preparation and phosphorus removal performance of iron tailings ceramsite - YU Xiaode; WANG Daohan (Gongye shui chuli)
The iron tailings ceramsite was prepared with iron tailings as the main raw material and fly ash as the auxiliary material, and the technological parameters were optimized through the raw material ratio experiment and orthogonal experiment. Based on adsorption isothermal model, thermodynamic parameters, kinetic model, and XRD, SEM, FT-IR, the adsorption process and adsorption mechanism of phosphorus on iron tailings ceramsite were analyzed. The results showed that the highest phosphorus adsorption rate of 98.81% was obtained when the mass ratio of iron tailings to fly ash was 9∶1, the preheating temperature was 400 ℃, the preheating time was 10 min, the roasting temperature was 900 ℃ and the roasting time was 20 min. Freundlich isothermal adsorption model and quasi-first-order kinetic equation could describe the adsorption behavior better, indicating that it belonged to the heterogeneous surface of multilayer adsorption, which was characterized by both physical diffusion and chemical adsorption, and the theoretical maximum adsorption capacity was 1.68 mg/g. The adsorption of phosphorus by iron tailings ceramsite was a spontaneous endothermic process. The characterization results showed that the surface of the iron tailings ceramsite was rough with rich mesoporous structure. The main crystal mineral was calcium-aluminum feldspar. After adsorption of phosphorus, a new phase was generated and attached to the surface of the ceramic particles, and the wave peaks in many places were weakened to different degrees. The adsorption mechanism of phosphorus by iron tailings ceramsite might be the sedimentation of Ca3(PO4)2 produced by calcium and magnesium plasma with phosphate and other precipitates, and the exchange of ligands between hydroxyl plasma and phosphate.